2021
DOI: 10.1039/d0na01037e
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally hazardous gas sensing ability of MoS2-nanotubes: an insight from the electronic structure and transport properties

Abstract: The ability of the (6,6) MoS2-nanotube (NT) to sense environmentally hazardous electrophilic and nucleophilic gases using density functional theory (DFT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The nature of the interaction existing between the donor orbital and acceptor orbital is expressed in terms of second-order perturbation energy ( E (2) ) or stabilization energy ( E (2) ). 42 A thorough literature review showed that the higher the stabilization energy the stronger the interaction between the donor orbital and acceptor orbital and the stronger the strength of adsorption of the sensing materials. 43 The second-order perturbation energy of the studied doped MoS 2 monolayer and its interaction with NH 3 gas was estimated using eqn (6) 44 where q i is the donor orbital occupancy, ε i , and ε j represent the diagonal elements and F ( i , j ) stands for the off-diagonal elements of the Fock matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the interaction existing between the donor orbital and acceptor orbital is expressed in terms of second-order perturbation energy ( E (2) ) or stabilization energy ( E (2) ). 42 A thorough literature review showed that the higher the stabilization energy the stronger the interaction between the donor orbital and acceptor orbital and the stronger the strength of adsorption of the sensing materials. 43 The second-order perturbation energy of the studied doped MoS 2 monolayer and its interaction with NH 3 gas was estimated using eqn (6) 44 where q i is the donor orbital occupancy, ε i , and ε j represent the diagonal elements and F ( i , j ) stands for the off-diagonal elements of the Fock matrix.…”
Section: Resultsmentioning
confidence: 99%
“…for strong electrostatic interactions. 61 For the purpose of this research, the obtained values of r(r) indicated an electrostatic interaction between the doped surface and the gas molecules. 62 Knowledge of V 2 r(r) shows that strong shared-shell interatomic interaction is evidenced by a local concentration of the electron density distribution at the critical point when V 2 r(r) < 0; on the other hand, weak closed-shell (CS) interaction exhibits local depletion when V 2 r(r) > 0.…”
Section: Bader Quantum Theory Of Atoms In Molecules (Qtaim)mentioning
confidence: 89%
“…This implies the excellent respective thermodynamic stability of our studied structures. As for the adsorption stability for Al-C 3 B at room temperature for both gases, we also calculate the adsorption energy according to eqn (1), where E sub+gas here is the total dynamic system energy, E sub here is the average total potential energy of Al-C 3 B in the first 10 ps at room temperature, and E gas is the average total potential energy of the gas in the first 10 ps at room temperature. The obtained adsorption energies versus the simulation time are given in Fig.…”
Section: Stability Analysis Of Al-c 3 Bmentioning
confidence: 99%
“…For human beings, air pollution also causes various problems. 1 Carbon dioxide (CO 2 ) is a byproduct of industrial and agricultural applications as well as fossil fuel combustion, and its excessive emission has become a serious challenge to human beings. As a critical factor for curbing global warming, the controlling and monitoring of CO 2 has drawn the attention of scholars worldwide.…”
Section: Introductionmentioning
confidence: 99%
“… 26 28 To boost the sensitivity of semiconductor-based gas sensors, low dimensionality and easily adjustable features of two-dimensional (2D) materials 29 31 have enchanted intensive research in inorganic 32 35 and organic 36 38 gas identification. 2D materials for example graphene, 39 43 phosphorene, 26 , 44 , 45 stanene, 46 48 arsenene, 49 silicone, 50 , 51 borophene, 52 , 53 molybdenum disulfide (MoS 2 ), 13 , 54 60 tungsten disulfide (WS 2 ) 61 monolayers have been investigated for the adsorption of small gas molecules and VOCs as well. Numerous compounds, elemental crystals, and atomically thin materials with exceptional electronic and mechanical properties are formed by lighter elements such as carbon (C), boron (B), and nitrogen (N).…”
Section: Introductionmentioning
confidence: 99%